STUDYING GENETIC EFFECTS IN NATURAL ECOSYSTEMS WITH APPLICATION OF A PLANT TEST OBJECT - E. A. Aghajanyan; R. E. Avalyan; A. L. Atoyants; A. E. Simonyan; R. M. Aroutiounian (Труды по прикладной ботанике, генетике и селекции)
The genotoxicity and clastogenic effects of water samples from Lake Sevan and the rivers of its basin with the application of Trad-SF (stamen filaments) and Trad-MN (micronuclei in the tetrads of microspores) bioassays of Tradescantia (clone 02) were investigated. A significant increase in the level of recessive mutation events (RME) frequency and micronuclei (MN) in tetrads from the water samples from the Gavaraget and Dzknaget Rivers as compared with the reference and other studied samples was detected. High positive correlation between the RME and MN frequencies and the concentration of some chemical elements in the studied water samples (Si, Al, P, Mn, Fe, and Cu) were revealed. The obtained results show that Trad-SF and Trad-MN tests of Tradescantia (clone 02) can be used for ecotesting of natural aquatic ecosystems in Armenia.